Pengaruh Lingkungan Kerja, Beban Kerja dan Komunikasi Terhadap Kepuasan Kerja Karyawan Pada CV. Putra Putri Jombang - Lailatus Sa’adah; Akhmad Taqiyuddin; Natasya Valeria (Jurnal Manajemen Riset Inovasi, 2024)
The aim of this study was to find out how the working environment, workload and communication affect the job satisfaction of employees at CV. Putra Putri Jombang. A quantitative methodology was used in this study. 40 employees form the population of this study while 40 respondents form the sample. A saturated sample was used in this research. The data was collected using a questionnaire and analyzed using SPSS version 26 multiple regression analysis. The results show that workload has a major impact on employee job satisfaction, work environment has a significant impact on employee job satisfaction and communication has a negligible impact on employee job satisfaction. The results of the coefficient of determination analysis showed 0.311 or 31.1%, which means that the variables work environment, workload and communication account for 31.1% of the variation in employee job satisfaction, while the remaining proportion is influenced by variables not included in this regression model.